2010
DOI: 10.1182/blood-2009-09-245274
|View full text |Cite
|
Sign up to set email alerts
|

Skin-draining lymph nodes contain dermis-derived CD103− dendritic cells that constitutively produce retinoic acid and induce Foxp3+ regulatory T cells

Abstract: Small intestinal CD103 ؉ dendritic cells (DCs) have the selective ability to promote de novo generation of regulatory T cells via the production of retinoic acid (RA). Considering that aldehyde dehydrogenase (ALDH) activity controls the production of RA, we used a flow cytometrybased assay to measure ALDH activity at the single-cell level and to perform a comprehensive analysis of the RA-producing DC populations present in lymphoid and nonlymphoid mouse tissues. RA-producing DCs were primarily of the tissue-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
297
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(325 citation statements)
references
References 50 publications
25
297
1
2
Order By: Relevance
“…Recently, Guilliams et al found expression of ALDH1 in macrophages in intestinal lamina propria, but did not report on their function (18). To our knowledge, this is the first report on ALDH1 + macrophages in humans, but failed to show the clinical implication.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Recently, Guilliams et al found expression of ALDH1 in macrophages in intestinal lamina propria, but did not report on their function (18). To our knowledge, this is the first report on ALDH1 + macrophages in humans, but failed to show the clinical implication.…”
Section: Discussionmentioning
confidence: 59%
“…To search for the presence of CICs in DLBCL, the ALDH1 + Recently, ALDH1 expression has been reported in murine DCs derived from the gut (17), lung (5) and dermis (18). In humans, there have been no reports on ALDH1 expression in DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pDC accumulation in lymphoid tissues, mucosa and organs occurs during several human pathologies, particularly in LN of patients affected by sarcoidosis, Mycobacterium tuberculosis infection [16], Kikuchi's disease [17], and in the skin of patients affected by psoriasis [18,19], systemic lupus erythematosus (SLE) [20] and lichen planus [21,22]. pDC accumulation has also been observed in brain lesions of patients with multiple sclerosis [23], in the salivary glands of patients with Sjogren's syndrome [24] and the synovia or inflamed muscle tissue/skin of people afflicted with rheumatoid arthritis [25,26] or dermatomyositis [27,28], respectively. pDC are over-represented in the blood of…”
Section: Discussionmentioning
confidence: 99%
“…Considering that RALDH expression is the only rate-limiting factor for RA production, Guilliams et al [27] used a flow cytometry-based assay to measure RALDH activity at the single-cell level and comprehensively analyzed RA-producing mouse DC populations. RA-producing DC were readily found in the skin and in the lungs, as well as the draining LN of these organs.…”
Section: Role Of Skin DC In the Induction Of Foxp3 1 Tregmentioning
confidence: 99%